2010
DOI: 10.1016/j.jfoodeng.2009.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Study of DIC hydrothermal treatment effect on rheological properties of standard maize (SMS), waxy maize (WMS), wheat (WTS) and potato (PTS) starches

Abstract: International audienceStandard maize (SMS), waxy maize (WMS), wheat (WTS) and potato (PTS) starches were hydrothermally treated by Instantaneous Controlled Pressure Drop (DIC) process at different pressure levels (1, 2 and 3 bar) corresponding to the temperatures of 100, 122 and 136 C, respectively. The rheological properties and particle size of treated starches under various conditions were compared to the native ones. The results showed for all starches, except for WTS, a reduction of the consistency coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The different effects of FIR on the n and K values of the starch gels might also be attributed to different crystallinity of starches. Similarly, it was reported that the effects of heat–moisture treatment and annealing on the n and K values of different starch gels were different, and this difference depended on the crystalline form and sources of starches …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The different effects of FIR on the n and K values of the starch gels might also be attributed to different crystallinity of starches. Similarly, it was reported that the effects of heat–moisture treatment and annealing on the n and K values of different starch gels were different, and this difference depended on the crystalline form and sources of starches …”
Section: Resultsmentioning
confidence: 91%
“…Similarly, it was reported that the effects of heat-moisture treatment and annealing on the n and K values of different starch gels were different, and this difference depended on the crystalline form and sources of starches. [27][28][29][30]…”
Section: Shear Dependence Of Starch Gelsmentioning
confidence: 99%
“…For treated cereal starches, there was a positive correlation of pressure and time to the transition temperatures. Moreover, a narrowing of the width of gelatinization endotherms into waxy maize starch was noted, increasing the enzymatic hydrolysis sensibility [63,65].…”
Section: Impact Of Instant Controlled Pressure-drop Treatment On Cereals Dryingmentioning
confidence: 96%
“…Yet, time reached a peak to further decrease viscosity, as part of the explanation is that the integrity of starch granules was preserved for all the conditions. Still, their crystalline organization changed, affecting their functional properties [63,65], yet for potato starch, the viscosity dramatically increased in all treatments [63]. As part of microstructure changes, standard maize starch and wheat starch complexes of amylose-lipid was formed at the treatments of 200 kPa for 60 min and 300 kPa for 30 s, respectively, without leaching amylose [63].…”
Section: Impact Of Instant Controlled Pressure-drop Treatment On Cereals Dryingmentioning
confidence: 99%
See 1 more Smart Citation